Microwave Assisted Synthesis and Evaluation of Toxicity and Antioxidant Activity of Pyrazoline Derivatives - Jasril Jasril; Hilwan Yuda Teruna; Aisyah Aisyah; Nurlaili Nurlaili; Rudi Hendra (Universitas Gadjah Mada, 2019)
Four pyrazoline analogues, 3-(4-methoxyphenyl)-5-naphthalene-1-yl-1-phenyl-4,5-dihydro-pyrazole (3), 3-(4-methoxyphenyl)-5-naphthalene-1-yl-4,5-dihydro-1H-pyrazole (4), 3-(2-methoxyphenyl)-5-naphthalene-1-yl-1-phenyl-4,5-dihydro-pyrazole (5) and 3-(2-methoxyphenyl)-5-naphthalene-1-yl-4,5-dihydro-1H-pyrazole (6) were synthesized via intermolecular cyclization between substituted chalcones and hydrazine derivatives. The compounds were synthesized in two steps. In the first step, the chalcones were synthesized by Claisen-Schmidt reaction. In the second step, they were cyclized with some hydrazine derivatives to form pyrazolines by using glacial acetic acid as a catalyst and assisted by microwave irradiation. The toxicity analysis showed that compound 1 and 2 were toxic with LC50 values of 11.47 and 0.97 μg/mL, respectively. Furthermore, only compound 6 showed high antioxidant activity by using DPPH with an IC50 value of 4.47 μg/mL.